The distribution of minerals in eluvio-iluvial horizon of agro soddy-podzolic soil - N. P. Chizhikova; E. B. Skvortsova; E. B. Varlamov; N. A. Churilin; A. E. Churilina; K. N. Abrosimov; A. V. Yudina; K. A. Romanenko (Бюллетень Почвенного института им. В.В. Докучаева)
The structure of micromonoliths from eluvial horizon (EL), transitional horizon (BEL) and iluvial horizon (BT1) of agro soddy-podzolic soil developed on clay loam mantle, underlain by non-calcareous moraine was studied. The following methods were applied: microtomography, x-ray diffractometry analyses, laser diffractometry, and soil particles sedimentation method. The objects are located on the experimental field of Zelenograd stationary related to Dokuchaev Soil Science Institute (Yeldigino village, Moscow Oblast). The method of computer tomography helped to determine the zones, from which the silty and clayey fragments of transitional horizon were extracted. The method of sedimentation allowedustomark the differences in the amount of fractions with sizes 10 mm. The method of x-ray diffractometry allowed us to determine the correlation of minerals in fractions with different particles sizes and also their qualitative composition. The minimal content of the clayey fraction is set is set in the sample from the eluvial part of the profile. The maximal content was set in the sample of separated clayey material from the transitional horizon. The most significant differences in the mineralogical composition are observed in the fraction lower than 1 mm. The eluvial part of the profile is characterized by the prevailing of hydromicasand chlorite vermiculite mixed-layer minerals. The same correlation of minerals is observed within the sample of silty part from the transitional layer. The iluvial part of the profile is characterized by the decrease of compounds with rigid structure (hydromicas, chlorite vermiculite). The clayey part of the transitional horizon is characterized by the highest content of silt and mica smectite within it. The distribution of fractions of fine (1-5 mm) and medium (5-10 mm) silt and their mineralogical content is less informative in relation to the differentiation of the soil profile during the podzolization.